Soil bulk density, porosity and penetration resistance recovery following timber harvest cessation on abandoned skid trails after 20 years, Kheyroud forest - Hadi Sohrabi; Meghdad Jourgholami; Baris Majnounian; Ghavamoddin Zahedi Amiri; Sattar Ezzati (تحقیقات جنگل و صنوبر ایران, 2015)
Deforestation and soil degradation start simultaneously, thus the conservation of forest and soil mutually affect each other.  Therefore, techniques should be developed to reduce the amount of forest damage which in turn shortens the recovery time. This study was conducted in two districts of Patom and Namkhaneh located in Kheyroud experimental forest, with the aim to assess the environmental impact of slope, traffic and rutting location on soil physical properties and its recovery over a 20-year period. Fourabandoned, downward skid trails of different ages were selected. In each skid trail, three traffic classes each divided into two slope classes were determined. For measurement of soil bulk density and total porosity, a sample plot of 10×4 m was established on each treatment. The results showed the maximum value of the bulk density and penetration resistance to be associated with high traffic intensity and > 20% slopes. Furthermore, soil bulk densities in different skid trails directions older than 20 years were more than those on the control treatment, yet the difference was not significant. However, the difference in resistance to penetration was significant. Over 20 years of skidding operations, soil physical properties have been retrieved, so that the bulk density and penetration resistance were 12.75 and 23.3% more than those in control area. Whereas this difference was not significant for bulk density, it showed significance for penetration resistance.